Unraveling another of the ‘Big Fiveʹ: new species and records of Cerithiopsidae from Brazil (Caenogastropoda: Triphoroidea) - Pimenta, Alexandre Dias; Faria, Raquel Garofalo De Souza; Figueira, Raquel Medeiros Andrade; Fernandes, Maurício Romulo (Zootaxa, 2024)
Despite being one of the most speciose marine mollusc families in the world, knowledge about the richness and distribution of Cerithiopsidae in Brazil is very limited. The present study aims to revise the occurrence of species of this family from Brazil, based on the examination of specimens in malacological collections obtained through several expeditions and surveys in the last years. All previous literature records of species from Brazil were checked, and the occurrence of Cerithiopsis gemmulosa, Cerithiopsis lata, Cerithiopsis io, Cerithiopsis fusiformis, Cerithiopsis capixaba, Cerithiopsis balaustium, Cerithiopsis aimen, Cerithiopsis prieguei, Cerithiopsis flava and Seila adamsii are confirmed; for these species, new information is presented regarding their distribution and shell morphology. The occurrence of Cerithiopsis greenii, Cerithiopsis iota, Cerithiopsis cynthiae and Horologica pupa in Brazil is rejected. Bittium brucei comb. nov. is reallocated in Cerithiopsis but considered a nomen dubium, due to the lack of features in the worn holotype, hindering its specific determination. Bittiolum guaranianum comb. nov., elsewhere considered a Cerithiopsis, is here considered to be a synonym of Bittiolum varium. Eight species, previously known from the Great Caribbean region, are recorded from Brazil: Cerithiopsis rabilleri, Cerithiopsis albovittata, Cerithiopsis hielardae, Cerithiopsis beneitoi, Cerithiopsis perigaudae, Cerithiopsis soubzmaignei comb. nov., Belonimorphis cubensis and Cubalaskeya nivea. Nine new species are proposed: Cerithiopsis pisinna sp. nov., Cerithiopsis aenea sp. nov., Cerithiopsis nimia sp. nov., Cerithiopsis claudioi sp. nov., Cerithiopsis vescula sp. nov., Cerithiopsis scobinata sp. nov., Cerithiopsis onerata sp. nov., Cerithiopsis parviscymnus sp. nov. and Cerithiopsis favus sp. nov. Besides that, Cerithiopsis cf. hielardae, Cerithiopsis cf. atalaya, Cerithiopsis sp. 1 and Dizoniopsis sp. are herein recognized as potential new species, pending acquisition of additional material for better understanding about their taxonomic status. Cerithiopsis gemmulosa, Cerithiopsis albovittata, Cerithiopsis flava (= Cerithiopsis redferni syn. nov.) and Seila adamsii are recognized as species complexes, with wide variation in shell morphology, and probably each of these complexes include various cryptic species in the western Atlantic. Summing up, 27 nominal species of Cerithiopsidae (in addition to four or five potential new species) are now recognized from Brazil, requiring further genetic investigation and additional sampling to improve the knowledge of this important group in this region.